The Venoarteriolar Reflex Significantly Reduces Contralateral Perfusion as Part of the Lower Limb Circulatory Homeostasis in vivo - Silva, Henrique; Ferreira, Hugo A.; da Silva, Hugo P.; Monteiro Rodrigues, L. (Frontiers in Physiology, 2018)
Perfusion at microvascular level involves the contribution of both local and central regulators, under a complex vascular signaling frame. The venoarteriolar reflex (VAR) is one of such regulatory responses, of particular relevance in the lower limb to prevent edema development. Although known for quite some time, many of the complex interactions involving all of these regulatory mechanisms still need clarification. Our objective was to look deeper into VAR through the Wavelet Transform (WT) spectral analysis of modern photoplethymography (PPG). Twelve healthy subjects (both sexes, 26.0 ± 5.0 y.o.) were enrolled in this study after informed written consent. Subjects were submitted to a leg lowering maneuver while lying supine to evoke the VAR, involving three phases – 10 minutes baseline register, both legs extended, 10 minutes challenge, with one randomly chosen leg (test) pending 50 cm below heart level, while the contralateral (control) remained in place, and 10 minutes recovery, resuming the initial position. PPG signals were collected from both feet and treated by the WT, revealing six spectral bands in frequency intervals comprising the cardiac [1.6-0.7 Hz], respiratory [0.4-0.26 Hz], myogenic [0.26-0.1 Hz], neurogenic / sympathetic [0.1-0.045 Hz], endothelial NO-dependent (NOd) [0.045-0.015 Hz] and NO-independent (NOi) [0.015-0.007 Hz] activities. For the first time, this approach revealed that, with VAR, perfusion significantly decreased in both limbs, although the change was more pronounced in the test foot. Here, a significant decrease in myogenic, neurogenic and NOd, were noted, while the control foot recorded a decrease in neurogenic and an increase in NOd. These results confirm the utility of WT spectral analysis for flowmotion. Further, it strongly suggests that VAR results from a complex cooperation between local myogenic-endothelial responses, where a central neurogenic reflex might also be involved.